RANCANG BANGUN MESIN PENGERING UNTUK PENGERINGAN LIMBAH SEAFOOD - Vendi Hermawan; Hari Purnomo (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
This Seafood waste drying process using a dryer that works still manually using the solar system energy. This study uses a participatory method in its implementation using FGD (focus group discussion) involving researchers, local communities, stakeholders and experts. From interviews with local residents, obtained the problems faced by the Trisik local people because of the abundance seafood waste. Thus the researchers create a waste dryers tool that easy to use, easy to maintainen, easy to operate, and using inexpensive materials. Components of this include the buffer dryer, pulleys parabolic player, parabola, and a drying rack. Buffer serves as a buffer parabola, a drying rack, and stand pulleys parabola player. The function of pulley parabolic player is to pointing, so that it gets the focus point of the solar cell. While the parabola which serves to reflect the solar cell to the drying rack so that the heat is evenly obtained. Drying rack consists of 4 stages that serves to put the waste. Finally, getting the tools that efficiently practical, economical and ergonomic.